The long-term patency of a gastroepiploic artery bypass graft deployed in a semiskeletonized fashion: predictors of patency. (10th January 2019) - Akita, Sho; Tajima, Kazuyoshi; Kato, Wataru; Tanaka, Keisuke; Goto, Yuki; Yamamoto, Ryota; Yazawa, Tubasa; Kozakai, Motoshi; Usui, Akihiko
Abstract: OBJECTIVES: Whether or not using the gastroepiploic artery (GEA) is associated with improved outcomes of coronary artery bypass grafting (CABG) remains unclear. Previous research has shown that the short-term function of the GEA was strongly associated with the degree of native vessel stenosis. We assessed the association between long-term GEA patency and the degree of stenosis of the coronary artery. METHODS: We retrospectively examined 517 patients who underwent CABG with an in situ semiskeletonized GEA from January 2000 to January 2015. In this cohort, 282 (54.5%) patients underwent distant radiological evaluations for >1 year post-surgery (range 1–18 years after surgery). Quantitative coronary angiography was used to measure the degree of stenosis of the native coronary artery. Preoperative angiographic parameters include the minimal lumen diameter (MLD) and the percentage of target vessel stenosis. A multivariable stepwise Cox proportional hazards regression analysis was used to identify predictors of angiographic occlusion. RESULTS: The cumulative patency rate of the GEA was 79.3% at 10 years. A multivariable analysis showed that an MLD (hazard ratio 4.43, 95% confidence interval 3.25–6.82; P  < 0.001) was an independent risk factor of GEA occlusion. A time-dependent receiver operating characteristic (ROC) curve analysis identified that an MLD >1 mm was set as the cut-off value for graft occlusion. Patients with an MLD <1 mm had a 10-year patency rate of 89.8%. CONCLUSIONS: The long-term patency of the semiskeletonized GEA was acceptable. The target vessel MLD obtained using quantitative coronary angiography was a strong predictor of patency. Good long-term patency can be expected for an MLD <1 mm.